Assessing the impact of Gliricidia agroforestry-based interventions on crop nutritional, antinutritional, functional, and mineral compositions in eastern Province, Zambia - Alamu, E.O.; Njoloma, J.; Akello, J.; Ngumayo, J.; Ray, C.; Mehreteab, T.; Chikoye, D.; Nyoka, I.; Dale, L.; Nagothu, U.S. (Informa UK Limited, 2023)
Agroforestry practices improve soil health which in turn improves crop nutrient concentrations and quality. This study examined how the agroforestry tree Gliricidia sepium intercropped with soybean, groundnuts, or maize affects crop nutrient compositions. The study was conducted in five Zambian chiefdoms for three crop-growing seasons (2019–2022) on 13 farmer-led demonstration trial sites. Seven treatments were tested that included maize, soybean, and groundnut plots with and without Gliricidia interventions. Grain samples were analyzed for crop nutrient contents using standard laboratory methods. Results showed that the treatments significantly (P < 0.05) improved maize nutritional properties except for crude fiber, total carbohydrate, and metabolizable energy. G. sepium intercropping with maize and soybean decreased the antinutritional contents and displayed better functional qualities. All elemental mineral components (except potassium, calcium, and sodium) were higher in the Gliricidia + maize intercrop than in the control treatment. The Gliricidia+soybean intercrop had lower mean mineral concentrations than the control (soybean only) except for Mg, Cu, and Zn. The Giliricidia+groundnut intercrop significantly increased groundnut mineral components except for Nitrogen, Phosphorus, Potassium, and Iron. It can be concluded that G. sepium intercropped with maize, soybean, and groundnuts significantly improved the crops’ nutritional quality.